Comparing the Perceived Orgasm Satisfaction and Responses to Orgasmic Difficulty of Heterosexual, Bisexual and Homosexual Women in New Zealand - Gavelle, Java Cristina Taina (Auckland University of Technology, 2022)
Introduction: This research will aim to compare the orgasmic satisfaction, orgasm difficulty and perceived partner response to orgasm difficulty women in New Zealand with different sexual orientations. The study uses a non-probability based convenience sampling in the form of an online self-report survey to gather information. Methods: The sample consisted of 667 women aged from 18 to 76 years old who identified as heterosexual, homosexual or bisexual. A Kruskal-Wallis was conducted to compare all three sexual orientation groups and orgasm satisfaction, orgasm difficulty and partner response to orgasm difficulty. More specific Mann-Whitney U tests followed these to see exactly where the differences lie between the groups. Results: There were no significant differences in orgasm satisfaction between the different sexual orientations. Significant differences in partner response to difficulty and orgasmic difficulties were observed across the different sexual orientation groups. Bisexual women reported the highest level of personal distress to orgasm difficulty, and both heterosexual and bisexual women reported higher levels of perceived partner distress to orgasm difficulty compared to homosexual women. Conclusion: This study contains several limitations; however, this study provides novel research into women of different sexual orientations and orgasm satisfaction, orgasm difficulty and perceived partner distress to orgasm difficulty.